The definitive guide to the OSCE the objective structured clinical examination as a performance assessment - Harden, Ronald M.; Lilley, Pat; Patricio, Madalena (Elsevier, 2016)
What is an OSCE? -- The inside story of the development of the OSCE -- The OSCE as the gold standard for performance assessment -- How the OSCE can contribute to the education programme -- What is assessed in an OSCE? -- Choosing a format for an OSCE -- The setting for an OSCE -- The patient -- The examiner -- Implementing an OSCE -- Evaluating the examinee's performance -- Providing feedback to the learner -- The examinee's perspective -- Evaluating an OSCE -- Costs and implementing an OSCE with limited resources -- Limitations of the OSCE -- Conclusions and looking to the future